A compartmental model of neuropeptide circulation and capture between the axon soma and nerve terminals. (17th February 2013) - Kuznetsov, I.A.; Kuznetsov, A.V.
SUMMARY This paper is motivated by a recent experimental research by Levitan and colleagues (Wong MY, Zhou C, Shakiryanova D, Lloyd TE, Deitcher DL, Levitan ES. Neuropeptide delivery to synapses by long‐range vesicle circulation and sporadic capture. Cell 2012; 148(5): 1029–1038), which discovered and explained the circulation of dense core vesicles (DCVs) between the neuron soma and nerve terminals. We developed a compartmental mechanistic model to simulate this circulation. The model includes five compartments, the axonal compartment and four en passant boutons, which are small axonal varicosities that are present in many axon terminals. By postulating expressions for DCV fluxes between the compartments and for the rates of DCV capture in the boutons and utilizing conservation of DCVs, ODEs modeling concentrations in each of the compartments were developed. The equations were then solved numerically. The obtained results provide insight into how DCV circulation develops, what the circulation is at steady state, and how it may be affected by defects in retrograde transport. Copyright © 2013 John Wiley & Sons, Ltd.